Managing the mismatch of water supply and demand in Selangor using Bayesian modelling considering climate change effect and hydroeconomic projection / Nurul Nadiah Mohd Firdaus Hum - Mohd Firdaus Hum, Nurul Nadiah (2019)
Water sustainability is a major concern in the state of Selangor. With the rapid increase in the population and its economic sectors, water supply availability has become crucial in meeting the state’s water consumer demands. To manage the mismatch between the water supply and demand in the state of Selangor, the study focused on three main objectives; to evaluate the raw water supply in the catchments focusing on the climatic changes and hydrometeorological aspects, to evaluate the treated water demand focusing on the economic aspects through hydroeconomic modelling and to apply Bayesian approach in modelling the imbalances by introducing water interventions. Two main catchments were chosen as study site; Selangor and Langat as it represents the major water supply in the state of Selangor. While, three main economic sectors; agriculture, city and industry were used in the study to capture the state’s main water consumer. Two scenarios were then simulated; Reference and High Population. Reference simulates business as usual while High Population simulates a population with a growth of 7%. Then, three main models were used in balancing the mismatch; climate change model, hydroeconomic model and Bayesian model. Climate change model simulates the climatic effect onto both catchments’ precipitation. With climate input, hydroeconomic model was used to model the demand side management via interventions for the economic sectors in balancing the mismatch. Bayesian model was then used to predict the probability of net improvement upon using the interventions. Results indicates that agriculture water demand in both Selangor and Langat catchments were well sustained through its water supply. However, deficit in water supply was detected for City and Industry sector for both Selangor and Langat catchments under Reference and High Population scenarios. Hydroeconomic model through demand side management was conducted with the supply and demand gap through the implementation of groundwater and water savings reduced by 62.24%, 57.37%, 98.13% 101.09% respectively in Selangor City Reference, Langat City Reference, Selangor Industry Reference and Langat Industry Reference. High population gap reduction was 97.70%, 24.43%, 173.34% and 3.75% in Selangor City-HP, Langat City-HP, Selangor Industry-HP and Langat Industry-HP. Then, to sustain the supply in meeting the demand, existing tariff need to be increase by 50% (Tariff C), large improvement needs to be conducted on the operation and maintenance (High operation and maintenance), water saving being fully implemented (High water saving) and water consumers are high in their awareness (High behaviour). Upon such actions, net improvement obtained were 99.3%. 99.2%, 100.0% and 99.9% respectively while the gap between supply and demand were reduced by 37.06%, 41.83%, 2.30% and 75.47% respectively. In conclusion, the water supply and demand mismatch in the state of Selangor can be balanced through increment in water tariff, improvement in the operation and maintenance, implementation of water savings and the change in the water consumers behaviour.